Autoimmune hepatitis in an Internal Medicine ward - Vaio, Teresa (2008)
Introduction: Autoimmune Hepatitis (AIH) is a hepatocellular inflammation of unknown cause, characterised by the presence of interface hepatitis on liver biopsy, and hypergammaglobulinaemia and autoantibodies in serum.Objective: To characterise clinical, laboratory and histological features, as well as the outcome, of AIH.Methods - Retrospective analysis of AIH cases admitted between 1987 and 2002 in an Internal Medicine Ward.Results: Twenty nine patients (pts), with a mean age of 34.2 ±16.4 years and a male-to-female ratio 1:28. The onset was fulminant in 6.9%, acute in 20.7% and insidious or chronic in 72.4%. Asthenia (65.6%), anorexia (48.3%), nausea and vomiting (48.3%), were the most common symptoms; 24.1% were asymptomatic. Applying the scoring system of the International Autoimmune Hepatitis Group, the diagnosis was definitive in 69% and probable in 31%. HAI type I was diagnosed in 86.2%, 3.5% were type II and in 10.3% none of the standard antibodies were found. Two pts were positive for anti-VHC, 1 for HbsAg and 1 had a recent history of hepatitis A. Initial therapy was prednisolone in 13 pts and prednisolone + azathioprine in 15. Complete response was achieved in 39.3%, partial response in 7.1%, failure in 25% and relapse in 28.6%. Four patients underwent liver transplantation. During a mean follow-up period of 69 months (range, 1 to 213 months), the mortality was 13.8%: 2 pts died from hepatic failure, 1 from sepsis and 1 from herpetic meningitis.Conclusions: At the time of diagnosis, 24.1% of the patients were asymptomatic and 27.1% had cirrhosis; therapy with prednisolone and azathioprine was more effective than prednisolone monotherapy; liver transplantation was required in 4 patients; the evolution was favourable in the majority of cases.